Diversity-Related, Student-Led National Medical Organizations: Leadership Opportunities for Learners - Nicholas N. Brutus; Dennis J. Spencer; Derek Huell; Yaritzy M. Astudillo; Austen Ott; Joyce H. Lee; Alec J. Calac; John P. Sánchez (MedEdPORTAL)
Introduction In light of the lack of diversity in academic medicine leadership, diversity-related, student-led national medical organizations (NMOs) provide a space for solace and reprieve among common peers while providing an opportunity to develop leadership competencies in a supportive environment. Despite the impact NMOs have had on cultivating generations of leaders in medicine, trainees may not identify opportunities for leadership development that are transferable to future careers in academic medicine. Methods We designed and implemented a dynamic 60-minute workshop with an interactive PowerPoint presentation, author-owned video testimonials (from past student leaders of NMOs), two case presentations, and reflection exercises. We assessed learner self-perceived confidence via workshop surveys. The target audience of this module was medical trainees, including medical students, residents, and fellows. Results Forty-three workshop attendees across three sites submitted partial or complete survey evaluations. Respondents included medical students (77%), with the remainder self-identified as either postbaccalaureate students, residents/fellows, academic faculty, or physicians. A comparison of pre- and postresponses showed a statistically significant increase in confidence in addressing each of the four educational objectives. Participants felt the case presentations offered relevant applicable examples. Discussion For many trainees, the role that diversity-related NMOs play in developing leadership competencies may be unclear and not articulated in traditional medical curricula. In this module, we provide examples of how NMOs facilitate leadership development and may encourage our diverse trainees to eventually become academic faculty.